What can technology add to the mathematics classroom?. (23rd December 2008) - Butler, Douglas; Milkova, Eva; Pozdilek, Martin
There are two basic influences of technology in the mathematics classroom: it can make a difference to how we teach and it can also affect what we teach. The latter is a huge area that is being well aired elsewhere. This article explores just a few ideas that have proved successful in bringing the subject to life in the classroom in ways which were impossible to imagine when we started teaching. They stem from the premise that a data projector and the internet connection are available in the classroom.